The Effects of Religion and Religiosity on Advertisement Assessment among Lebanese Consumers - Farah, Maya F. (2014)
Religion plays a significant role in the way consumers perceive the advertising of controversial products. Religiosity, which describes an individual's commitment and adherence to religious values and beliefs, is also of a noteworthy relevance in how consumers appraise product advertisements. Conducted in Lebanon, the study employed a survey design that was administered to a randomized sample including respondents from the two main religions in the country, namely Islam and Christianity. The questionnaire was completed by a representative sample of 527 Lebanese consumers. Those sampled from each region were chosen based on religious sects’ distribution in each of the five local conglomerates, with a fair representation of gender and age groups. The results indicated significant differences in perceptions between Muslim and Christian, and highly religious versus less religious respondents with regards to the offensiveness of the advertising of controversial products. Briefly, the more religious consumers were largely more offended by the advertisement of the 17 products studied than nonreligious consumers. Also, Muslim consumers from both sects, showed greater level of offense than their Christian counterparts. These results have significant implications on both advertisers and marketing managers aiming to expand their field of business in the Middle East, as well as in other international regions where religion plays an integral role in the society.